2016
DOI: 10.3109/13816810.2015.1039893
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Macular Changes in the First Proband of Autosomal Dominant Vitreoretinochoroidopathy (ADVIRC) Due to a Newly Identified Mutation inBEST1

Abstract: Progressive posterior chorioretinal changes occurred over time in the initial ADVIRC proband, leading to visual loss. The causative mutation in this patient falls in the transmembrane domain of the BEST1 protein, with unclear functional consequences. Although previous studies showed alteration in pre-mRNA splicing, in vitro splicing assays failed to demonstrate this in our patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Further studies have shown that there can be a progression of the fundus findings with downstream development of central cone dysfunction. Similar progression in the posterior pole has also been noted (Chen and Goldberg, 2016; Chen et al, 2016; Oh and Vallar, 2006). In 2004, Yardley et al described five families with ADVIRC and nanophthalmos that were genetically linked to mutations in BEST1 (Yardley et al, 2004).…”
Section: Clinical Spectrum Of the Bestrophinopathiessupporting
confidence: 78%
“…Further studies have shown that there can be a progression of the fundus findings with downstream development of central cone dysfunction. Similar progression in the posterior pole has also been noted (Chen and Goldberg, 2016; Chen et al, 2016; Oh and Vallar, 2006). In 2004, Yardley et al described five families with ADVIRC and nanophthalmos that were genetically linked to mutations in BEST1 (Yardley et al, 2004).…”
Section: Clinical Spectrum Of the Bestrophinopathiessupporting
confidence: 78%
“…In this system, the c.704T > C (p.V235A) mutation resulted in the duplication of Exon 6 27 . However, recent investigations into a novel mutation (pG83D) using the same minigene assay in HEK293 cells failed to show any effect on splicing 4 . To test the hypothesis that alterations in splicing cause ADVIRC, we assessed transcript expression in iPSC-RPE cells from patients harbouring the pV235A mutation.…”
Section: Discussionmentioning
confidence: 92%
“…Autosomal dominant vitreoretinochoroidopathy (ADVIRC–OMIM 193220) is a rare retinal dystrophy characterised by distinct fundus appearance with a circumferential ring of retinal atrophy and pigmentation in the far peripheral retina 1 2 3 . The macula is usually normal at diagnosis but cystoid macular oedema and macular atrophy may occur over time 4 . Other ocular features include cataract, angle closure glaucoma, fibrillar condensation of the vitreous, retinovascular abnormalities and developmental abnormalities, such as nanophthalmos and microcornea 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These contradictory results could suggest that proper BEST1 localization or a failure to correctly traffic to the cell membrane is rather mutation-dependent than an ADVIRC-specific characteristic and further underscores the necessity to model additional ADVIRC mutations on the basis of the hiPSC-RPE cell culture model. Furthermore, studies have shown that ADVIRC mutations p.(V86M), p.(Y236C), p.(V239M), and p.(V235A) affect BEST1 mRNA splicing using a minigene assay in HEK293 cells [8,46] while ADVIRC mutation p.(G83D) failed to exhibit any effect on mRNA splicing [47]. In the present study, we found no evidence for alternative splicing in the ADVIRC-associated hiPSC-RPE cell lines well in agreement with earlier findings from Carter et al [35].…”
Section: Discussionmentioning
confidence: 99%